Controlled ring-opening polymerisation using microwave heating - Deng, Ei Leen (2016)
This thesis reports the synthesis of linear and star polycaprolactone via the ring-opening polymerisation of ε-caprolactone using R–OH / tin octanoate as the initiator / catalyst system. The aim of the work carried out in this thesis is to study the polymerisation when conducted using both conventional and microwave heating and develop new synthetic methods for the synthesis of structural polymers via ring-opening polymerisation.